2020
DOI: 10.1111/jog.14190
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA PVT1 enhances cell proliferation but inhibits apoptosis through sponging microRNA‐149 in epithelial ovarian cancer

Abstract: Aim This study aimed to investigate the influence of circular RNA PVT1 (circ‐PVT1) on epithelial ovarian cancer (EOC) cell proliferation and apoptosis, more importantly, to identify the target microRNAs (miRNA) of circ‐PVT1 in EOC. Methods Circ‐PVT1 expression in EOC cell lines and nonmalignant control cells was detected. Cell proliferation, apoptosis and candidate target miRNA (miR‐149, miR‐183 and miR‐194) expressions were detected in circ‐PVT1 overexpression treated CAOV3 cells and circ‐PVT1 knock‐down trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…CircRNAs have been found to be a type of key regulators in cancers. It has been found that circular PVT1 is a carcinogenic non-coding RNA and has important clinical significance in numerous carcinoma including ovarian cancer, gastric cancer and thyroid cancer [33][34][35][36][37][38][39][40][41][42]. For example, reduced circular RNA circPVT1 retarded gastric cancer growth via microRNA-3666-mediated reduced SIRT7 level [43].…”
Section: Discussionmentioning
confidence: 99%
“…CircRNAs have been found to be a type of key regulators in cancers. It has been found that circular PVT1 is a carcinogenic non-coding RNA and has important clinical significance in numerous carcinoma including ovarian cancer, gastric cancer and thyroid cancer [33][34][35][36][37][38][39][40][41][42]. For example, reduced circular RNA circPVT1 retarded gastric cancer growth via microRNA-3666-mediated reduced SIRT7 level [43].…”
Section: Discussionmentioning
confidence: 99%
“…Several circRNAs (such as circEPSTI1, circGFRA1, circ0051240, circPIP5K1A, circPVT1 and circABCB10) have been found to increase the proliferative and invasive capacities of OC cells by acting as miRNA sponges [ 121 , 122 , 123 , 124 , 125 , 126 ]. Knockdown of circSMAD7 by short-hairpin RNA (shRNA) was associated with decreased cell proliferation, migration and invasion and with increased expression of KLF6 in CC cells [ 127 ].…”
Section: The Expression Functions and Mechanisms Of Circrnas In Gmentioning
confidence: 99%
“…CircPVT1 is generated from exon 2 of the PVT1 gene and has been widely recognized to act as oncogene in several tumors [ 12 ]. In epithelial ovarian cancer, researchers revealed that circPVT1 expression was upregulated and enhanced cell proliferation but inhibited cell apoptosis through sponging microRNA-149 [ 13 ]. In gastric cancer (GC), circPVT1 contributed to paclitaxel resistance of GC cells through regulating ZEB1 expression by sponging to miR-124-3p [ 14 ].…”
Section: Introductionmentioning
confidence: 99%